Assessment of Cardiovascular Apoptosis in the Isolated Rat Heart by Magnetic Resonance Molecular Imaging - Karl-Heinz Hiller; Christiane Waller; Matthias Nahrendorf; Wolfgang R. Bauer; Peter M. Jakob (Molecular Imaging)
Apoptosis, an active process of cell self-destruction, is associated with myocardial ischemia. The redistribution of phosphatidylserine (PS) from the inner to the outer leaflet of the cell membrane is an early event in apoptosis. Annexin V, a protein with high specificity and tight binding to PS, was used to identify and localize apoptosis in the ischemic heart. Fluorescein-labeled annexin V has been used routinely for the assessment of apoptosis in vitro. For the detection of apoptosis in vivo, positron emission tomography and single-photon emission computed tomography have been shown to be suitable tools. In view of the relatively low spatial resolution of nuclear imaging techniques, we developed a high-resolution contrast-enhanced magnetic resonance imaging (MRI) method that allows rapid and noninvasive monitoring of apoptosis in intact organs. Instead of employing superparamagnetic iron oxide particles linked to annexin V, a new T 1 contrast agent was used. To this effect, annexin V was linked to gadolinium diethylenetriamine pentaacetate (Gd-DTPA)-coated liposomes. The left coronary artery of perfused isolated rat hearts was ligated for 30 min followed by reperfusion. T 1 and T 2 * images were acquired by using an 11.7-T magnet before and after intracoronary injection of Gd-DTP-labeled annexin V to visualize apoptotic cells. A significant increase in signal intensity was visible in those regions containing cardiomyocytes in the early stage of apoptosis. Because labeling of early apoptotic cell death in intact organs by histological and immunohistochemical methods remains challenging, the use of Gd-DTPA-labeled annexin V in MRI is clearly an improvement in rapid targeting of apoptotic cells in the ischemic and reperfused myocardium.